New PCR systems to confirm real-time PCR detection of Mycobacterium avium subsp. paratuberculosis - Bölske Göran; Herthnek David (BMC Microbiology, 2006)
Abstract Background Johne's disease, a serious chronic form of enteritis in ruminants, is caused by Mycobacterium avium subsp. paratuberculosis (MAP). As the organism is very slow-growing and fastidious, several PCR-based methods for detection have been developed, based mainly on the MAP-specific gene IS900. However, because this gene is similar to genes in other mycobacteria, there is a need for sensitive and reliable methods to confirm the presence of MAP. As described here, two new real-time PCR systems on the IS900 gene and one on the F57 gene were developed and carefully validated on 267 strains and 56 positive clinical faecal samples. Results Our confirmatory PCR systems on IS900 were found sensitive and specific, only yielding weak false positive reactions in one strain for each system. The PCR system on F57 did not elicit any false positives and was only slightly less sensitive than our primary IS900-system. DNA from both naturally infected and spiked faeces that tested positive with our primary system could be confirmed with all new systems, except one low-level infected sample that tested negative with the F57 system. Conclusion We recommend using the newly constructed DH3 PCR system on the F57 gene as the primary confirmatory test for PCR positives, but should it fail due to its lower sensitivity, the DH1 and DH2 PCR systems should be used.